2010
DOI: 10.1262/jrd.09-108h
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cryotop and Solid Surface Vitrification Methods for the Cryopreservation of In Vitro Matured Bovine Oocytes

Abstract: Abstract. The aim of the present study was to compare the efficacies of the cooling systems of the solid surface (SSV) and Cryotop vitrification methods for cryopreservation of bovine oocytes at the metaphase II stage. The effects of vitrification on oocyte viability, in vitro fertilization (IVF), pronucleus formation and subsequent in vitro development were assessed. In vitro matured (IVM) bovine oocytes were subjected to equilibration and vitrification solutions according to the SSV method, and then the oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 38 publications
5
29
4
1
Order By: Relevance
“…Interestingly, in human oocytes the completion of rehydration occurs after 3 h culture [33]. This is in line with the usual protocols of laboratory for oocytes fertilization, which typically includes about a 2 h warming phase before oocytes exposure to spermatozoa [34, 35]. …”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, in human oocytes the completion of rehydration occurs after 3 h culture [33]. This is in line with the usual protocols of laboratory for oocytes fertilization, which typically includes about a 2 h warming phase before oocytes exposure to spermatozoa [34, 35]. …”
Section: Discussionmentioning
confidence: 70%
“…Relatively higher yields of bovine blastocysts 7 to 8 days after IVF in the fresh ovary group, compared with general yields as 20-40% reported in conventional bovine IVF 185 (Iwata et al, 2005;Rizos et al, 2002;Sripunya et al, 2010), may be due to the selected use of maturation-confirmed oocytes after removal of cumulus cells for subsequent IVF, instead of COCs with unknown maturation rate.…”
Section: Discussionmentioning
confidence: 77%
“…Pemakaian krioprotektan ekstraseluler dalam konsentrasi yang optimal akan mencegah kerusakan morfologi oosit pada saat proses vitrifikasi. 14,15 . Pada konsentrasi sukrosa 0,5 M, penggunaan sukrosa kurang mencukupi sehingga tidak mampu menjaga kestabilan membran oosit pada saat peristiwa dehidrasi.…”
Section: Pembahasanunclassified